2014
DOI: 10.1371/journal.pone.0103029
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcome after Complicated Shiga Toxin–Producing Escherichia coli Infection

Abstract: BackgroundThe diarrhea associated hemolytic uremic syndrome (HUS) is a major cause of acute uremic failure in children, but not very common in adults. The enterohaemorrhagic Escherichia coli -epidemic in Germany in 2011 affected mostly young and healthy adults. While their immediate deficits have been published, not much is known about the time course and degree of recovery concerning cognitive and behavioral impairment.Methods and FindingsTwenty patients with Shiga toxin –producing Escherichia coli infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, numerous deficits of patients with Stx2-associated HUS can be explained by its dysfunction. Consequentially, patients' relatively good neurological and neuropsychological outcome can be clarified by the thalamic recovery [11,13,14,34]. Neurological and neuropsychological impairments of our patients are however enormous in comparison to their subtle microstructural thalamic alterations.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, numerous deficits of patients with Stx2-associated HUS can be explained by its dysfunction. Consequentially, patients' relatively good neurological and neuropsychological outcome can be clarified by the thalamic recovery [11,13,14,34]. Neurological and neuropsychological impairments of our patients are however enormous in comparison to their subtle microstructural thalamic alterations.…”
Section: Resultsmentioning
confidence: 89%
“…However, additional detailed neuropsychological and neuromotor performance tests might reveal further impairment after HUS [13,31,32]. A neuropsychological analysis of adults affected during the 2011 outbreak did not show significant deficits 1 year after STEC infection [33].…”
Section: Discussionmentioning
confidence: 86%
“…A recent study that assessed 20 adult patients ∼3 months and 1 year after the acute disease, reported cognitive impairment in almost half of the patients 1 year after infection. 27 Here again fatigue, psychomotor slowing, and concentration problems were reported frequently. Of note, the neuropsychological assessment was performed at 1 year only in those patients and in those tests where results below average had been observed in the first follow-up 10 to 30 weeks after disease onset.…”
Section: Discussionmentioning
confidence: 94%